Treatment of Surgical Brain Injury by Immune Tolerance Induced by Peripheral Intravenous Injection of Biotargeting Nanoparticles Loaded With Brain Antigens - Tian, Zhen; Xu, Lixia; Chen, Qian; Feng, Ruoyang; Lu, Hao; Tan, Huajun; Kang, Jianming; Wang, Yinsong; Yan, Hua (Frontiers in Immunology, 2019)
Once excessive, neurological disorders associated with inflammatory conditions will inevitably cause secondary inflammatory damage to brain tissue. Immunosuppressive therapy can reduce the inflammatory state, but resulting infections can expose the patient to greater risk. Using specific immune tolerance organs or tissues from the body, brain antigen immune tolerance treatment can create a minimal immune response to the brain antigens that does not excessively affect the body's immunity. However, commonly used immune tolerance treatment approaches, such as those involving the nasal, gastrointestinal mucosa, thymus or liver portal vein injections, affect the clinical conversion of the therapy due to uncertain drug absorption or inconvenient routes of administration. If hepatic portal intravenous injections of brain antigens could be replaced by normal peripheral venous infusion, the convenience of immune tolerance treatment could certainly be greatly increased. We attempted to encapsulate brain antigens with minimally immunogenic nanomaterials, to control the sizes of nanoparticles within the range of liver Kupffer cell phagocytosis and to coat the antigens with a coating material that had an affinity for liver cells. We injected these liver drug-loaded nanomaterials via peripheral intravenous injection. With the use of microparticles with liver characteristics, the brain antigens were transported into the liver out of the detection of immune armies in the blood. This approach has been demonstrated in rat models of surgical brain injury. It has been proven that the immune tolerance of brain antigens can be accomplished by peripheral intravenous infusion to achieve the effect of treating brain trauma after operations, which simplifies the clinical operation and could elicit substantial improvements in the future.